Conversion rate optimization - King, Andrew B. (O'Reilly, 2017)
Remember when an optimized website was one that merely didn't take all day to appear? Times have changed. Today, website optimization can spell the difference between enterprise success and failure, and it takes a lot more know-how to achieve success. This book is a comprehensive guide to the tips, techniques, secrets, standards, and methods of website optimization. From increasing site traffic to maximizing leads, from revving up responsiveness to increasing navigability, from prospect retention to closing more sales, the world of 21st century website optimization is explored, exemplified and explained. Website Optimization combines the disciplines of online marketing and site performance tuning to attain the competitive advantage necessary on today's Web. You'll learn how to improve your online marketing with effective paid and natural search engine visibility strategies, strengthened lead creation and conversion to sales methods, and gold-standard ad copywriting guidelines. Plus, your increased site speed, reduced download footprint, improved reliability, and improved navigability will work synergistically with those marketing methods to optimize your site's total effectiveness.